Epstein-Barr Virus as a promising immunotherapeutic target for nasopharyngeal carcinoma treatment - Teow, Sin Yeang *; Yap, Hooi Yeen *; Peh, Suat Cheng * (Hindawi Publishing, 2017)
Epstein-Barr virus (EBV) is a pathogen that infects more than 90% of global human population. EBV primarily targets Blymphocytes and epithelial cells while some of them infect monocyte/macrophage, T-lymphocytes, and dendritic cells (DCs). EBV infection does not cause death by itself but the infection has been persistently associated with certain type of cancers such as nasopharyngeal carcinoma (NPC), Burkitt’s lymphoma (BL), and Hodgkin’s lymphoma (HL). Recent findings have shown promise on targeting EBV proteins for cancer therapy by immunotherapeutic approach. Some studies have also shown the success of adopting EBV-based therapeutic vaccines for the prevention of EBV-associated cancer particularly on NPC. In-depth investigations are in progress to refine the current therapeutic and vaccination strategies. In present review, we discuss the highly potential EBV targets for NPC immunotherapy and therapeutic vaccine development aswell as addressing the underlying challenges in the process of bringing the therapy and vaccination from the bench to bedside.